The Impact of Race on Perioperative and Patient-Reported Outcomes following Autologous Breast Reconstruction. Issue 1 (21st December 2021) - Oskar, Sabine; Nelson, Jonas A.; Hicks, Madeleine E. V.; Seier, M.S., Kenneth P.; Tan, Kay See; Chu, Jacqueline J.; West, Scott; Allen, Robert J.; Barrio, Andrea V.; Matros, Evan; Afonso, Anoushka M.
Abstract : Background: Racial disparities are evident in multiple aspects of the perioperative care of breast cancer patients, but data examining whether such differences translate to clinical and patient-reported outcomes are limited. This study examined the impact of race on perioperative outcomes in autologous breast reconstruction. Methods: A retrospective cohort study including all breast cancer patients who underwent immediate autologous breast reconstruction at a single institution from 2010 to 2017 was conducted. Self-reported race was used to classify patients into three groups: white, African American, and other. The primary and secondary endpoints were occurrence of any major complications within 30 days of surgery and patient-reported outcomes (measured with the BREAST-Q), respectively. Regression models were constructed to identify factors associated with the outcomes. Results: Overall, 404 patients, including 259 white (64 percent), 63 African American (16 percent), and 82 patients from other minority groups (20 percent), were included. African American patients had a significantly higher proportion of preoperative comorbidities. Postoperatively, African American patients had a higher incidence of 30-day major complications ( p = 0.004) and were more likely to return to the operating room ( p = 0.006). Univariable analyses examining complications demonstrated that race was the only factor associated with 30-day major complications ( p = 0.001). Patient-reported outcomes were not statistically different at each time point through 3 years postoperatively. Conclusions: African American patients continue to present with increased comorbidities and may be more likely to experience major complications following immediate autologous breast reconstruction. However, patient-reported satisfaction or physical well-being outcomes may not differ between groups. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.